(untitled) (Bangladesh Medical Journal, 2014)
Adenotonsillectomy is one of the commonly performed operations in children. Daycare adenotonsillectomy is common in many parts of the world but it is not a common practice in major hospitals of our country due to fear of complications. 105 children within 6-12 years of age with a range of 8.8 ± 1.4 years (mean ± SD) underwent daycare adenotonsillectomy in between April 2000 to September 2001. Reactionary hemorrhage is found in 1.9% cases and secondary hemorrhage in 0.9% cases. None required return to the operation theatre. 95.2% cases were discharged 8-12 hours after operation with a stay of 10.2 ± 1.4 hours (mean ± SD). 5 patients required admission for overnight observation and treatment for complications. There was no mortality. The incidence of complication is low and comparable to other studies. The result suggests that daycare adenotonsillectomy can be safely performed in properly selected children. DOI: http://dx.doi.org/10.3329/bmj.v42i1.18971 Bangladesh Med J. 2013 Jan; 42 (1): 11-13